Alteration of the level of salivary cortisol under psychological stress and its relationship with rumination and personality traits - S Sadegh-Nejadi; R Afrisham; O Soliemanifar; W Kooti; M Aberomand; S Najjar-Asl; A Khaneh-Keshi (مجله دانشگاه علوم پزشکی گرگان, 2017)
Background and Objective: Gender differences in biobehavioral responses to environmental stressors and experience of psychological stress should be identified. This study was done to evaluate the changes of the level of salivary cortisol under psychological stress and its relationship with rumination and personality traits.